Randomized phase II study of modified FOLFOX-6 in combination with ramucirumab or icrucumab as second-line therapy in patients with metastatic colorectal cancer after disease progression on first-line irinotecan-based therapy. (22nd December 2016) - Moore, M.; Gill, S.; Asmis, T.; Berry, S.; Burkes, R.; Zbuk, K.; Alcindor, T.; Jeyakumar, A.; Chan, T.; Rao, S.; Spratlin, J.; Tang, P. A.; et al.
Abstract : In this phase II study in patients with metastatic colorectal cancer following disease progression on first-line irinotecan-based therapy, combining ramucirumab or icrucumab with mFOLFOX-6 did not achieve the primary end point of improvement in progression-free survival. Abstract : Background: Icrucumab and ramucirumab are recombinant human IgG1 monoclonal antibodies that bind VEGF receptors 1 and 2 (VEGFR-1 and -2), respectively. This randomized phase II study evaluated the antitumor activity and safety of icrucumab and ramucirumab each in combination with mFOLFOX-6 in patients with metastatic colorectal cancer after disease progression on first-line therapy with a fluoropyrimidine and irinotecan. Patients and methods: Eligible patients were randomly assigned to receive mFOLFOX-6 alone (mFOLFOX-6) or in combination with ramucirumab 8 mg/kg IV (RAM+mFOLFOX-6) or icrucumab 15 mg/kg IV (ICR+mFOLFOX-6) every 2 weeks. Randomization was stratified by prior bevacizumab therapy. The primary end point was progression-free survival (PFS). Secondary end points included overall survival (OS), tumor response, safety, and PK. Results: In total, 158 patients were randomized, but only 153 received treatment (49 on mFOLFOX-6, 52 on RAM+mFOLFOX-6, and 52 on ICR+mFOLFOX-6). Median PFS was 18.4 weeks on mFOLFOX-6, 21.4 weeks on RAM+mFOLFOX-6, and 15.9 weeks on ICR+mFOLFOX-6 (RAM+mFOLFOX-6 versus mFOLFOX-6, stratified hazard ratio [HR] 1.116 [95% CI 0.713–1.745], P = 0.623; ICR+mFOLFOX-6 versus mFOLFOX-6, stratified HR 1.603 [95% CI 1.011–2.543], P = 0.044). Median survival was 53.6 weeks on mFOLFOX-6, 41.7 weeks on RAM+mFOLFOX-6, and 42.0 weeks on ICR+mFOLFOX-6. The most frequent adverse events reported on the ramucirumab arm (RAM+mFOLFOX-6) were fatigue, nausea, and peripheral sensory neuropathy; those on the icrucumab arm (ICR+mFOLFOX-6) were fatigue, diarrhea, and peripheral sensory neuropathy. Grade ≥3 serious adverse events occurred at comparable frequency across arms. Conclusions: In this study population, combining ramucirumab or icrucumab with mFOLFOX-6 did not achieve the predetermined improvement in PFS. ClinicalTrials.gov: NCT01111604.